PELATIHAN MANAJEMEN KEUANGAN UNTUK MENINGKATKAN KAPASITAS PELAKU UMKM DI KELURAHAN PADDUPPA KECAMATAN TEMPE KABUPATEN WAJO - Yuniarti, A.; Jamaluddin, Andi; -, Faisal; Nurwana, Andi (Unit Publikasi dan Jurnal Sekolah Tinggi Ilmu Ekonomi Tri Dharma Nusantara Makassar, 2022)
The SMEs peddled their business in the Container Village by the Padduppa Village Government, Tempe District, Wajo Regency. Kampung Container located on the Cenrana River Street is a place designed by the government so that it attracts all culinary connoisseurs and a place to relax for visitors who want to enjoy the beauty of the coast of Lake Tempe and the Cenrana River Flow. The MSMEs are domiciled in Padduppa Village, facilitated by the government to increase their productivity and business results. These MSME actors have been active in their business since 2018. But in financial management but still minimal and still manually so that sometimes the SMEs are difficult to manage their finances, addressing the development of the business of MSMEs in the Padduppa Village who are increasingly advanced and crowded by visitors so that they really need knowledge about regulating business finances so that SMEs continue to exist in his efforts without being burdened with financial problems and can be managed professionally for the welfare of MSME actors. The purpose of financial management education for SMEs is (1) MSME actors can maximize profits with The right decision (2) Utilization of the right and optimal money so that efficiency is maintained. (3) Efficiency so that financial distribution is appropriate in all aspects or financial control, this activity is carried out on Thursday, May 12, 2022, at the Padduppa Village Office Hall, Tempe District, Wajo Regency. The results obtained are (1) MSME actors are able to plan, regulate, direct, and supervise financial activities such as procurement and utilization of their business funds (2) MSME actors are able to estimate the needs and composition of capital (3) the level of participation of MSMEs is quite good, so The activities carried out can provide an overview of the benefits of financial management such as determining investment appropriately